Effective resource virtualization for dynamic IoT devices in road network - Padmanabhan P.; Sampath Kumar K.; John A. (Institute of Advanced Engineering and Science, 2023)
Internet of things (IoT), which is considerably innovating and generating a large volume of processes in every field worldwide, is one of the recent and next disruptive technologies. As a result, IoT devices and others are increasing network connections in the relevant field. It is essential to maximize and process these kinds of resources. The effective usage of resources is one of the most important and very difficult to manage the resource in the dynamic environments. Many studies are performed in the effective usage of resource in the static and dynamic environments. However, the dynamic environments have still different issues and have to solve different dynamic networking issues. In this work, present a mechanism for managing different connecting devices in the dynamic environments. Especially this system is concentrating on road network device management in dynamic environments. The proposed system called dynamic road sensing (DyRSen) connectivity is support to different continuous connectivity. The DyRSen provides: i) continuous connectivity using available resources and provide virtual environment for computing, ii) temporary data storage in dynamic environment for effective resource sharing, and iii) reduce the energy utilization and network overhead and the effective resource management is compared to the other works.